Exploring Story Selection Influences at the British Broadcasting Corporation. (September 2016) - Watson, W. Joe
This study explores the influences on story selection at the British Broadcasting Corporation (BBC). Through interviews with personnel across all levels of BBC News and observation of editorial meetings and newsroom routines at BBC World Headquarters in London, the author applies Gatekeeping theory in an effort to understand the BBC's story selection process. Three themes emerge to inform our understanding of how stories are chosen and shaped for coverage at the BBC: respect and appreciation of the audience, the needs of individual networks and programs, and awareness of the Royal Charter.